Short‐term results of acellular porcine corneal stroma keratoplasty for herpes simplex keratitis. (10th April 2019) - Zheng, Jiao; Huang, Xiaodan; Zhang, Yue; Wang, Yi; Qin, Qiyu; Lin, Lin; Jin, Xiuming; Lam, Ching; Zhang, Jinnan
Abstract: Background: Corneal transplantation is a common surgical intervention for restoring vision loss due to corneal damages. However, for cultural reasons, there is a huge shortage of donor corneas in China. Acellular porcine corneal stromas (APCSs) can be used as corneal substitutes in lamellar keratoplasty for corneal ulcers. This study was conducted to analyze the results of APCS use for herpes simplex keratitis (HSK). Methods: The study involved HSK patients who underwent keratoplasty with APCSs from February 2016 to October 2017 in the second affiliated hospital of Zhejiang University. Patient data were collected at 7 days, 1 month, 3 months, 6 months, and at the last follow‐up (7‐25 months) postoperative. The corneal transparency, neovascularization, visual acuity, and graft stability were observed. Results: Thirteen patients with HSK including five patients with corneal perforation were included in this study, nine patients underwent deep anterior lamellar keratoplasty (DALK) and five perforation patients underwent double lamellar keratoplasty. There were nine men and four women with an average age of 62.5 ± 5.6 years old (ranging from 52 to 70 years old). The mean postoperative follow‐up duration was 15.1 ± 5.8 months (ranging from 7 to 25 months). At the last visit, visual acuity improved in nine patients (69.2%) compared with preoperative ( P = 0.008).The grafts of seven individuals (53.8%) were completely transparent or slightly opaque; their corneal transparency score had improved significantly compared with before the surgery ( P = 0.010). Various degrees of neovascularization were present in 11 of the 13 patients (84.6%), most neovascularization gradually stabilized. Graft dissolution occurred in three eyes (23.1%) during the observation period, two underwent regrafting, the other one became stable after treatment. Three patients underwent second allograft transplantation, two of which encountered APCS graft dissolution and one of the patients requested a human donor allograft transplantation due to transparency issues despite the absence of adverse issues. Conclusion: Acellular porcine corneal stroma seems to be effective in the treatment of HSK and can be used in HSK with corneal perforation by using double lamellar keratoplasty in an emergency.